Application of Polyethylene Glycol to Promote Cellular Biocompatibility of Polyhydroxybutyrate Films - Rodman T. H. Chan; Helder Marçal; Robert A. Russell; Peter J. Holden; L. John R. Foster (International Journal of Polymer Science)
Polyhydroxybutyrate (PHB) is a biomaterial with potential for applications in biomedical and tissue engineering; however, its brittle nature and high crystallinity limit its potential. Blending PHB with a variety of PEGs produced natural-synthetic composite films composed of FDA-approved polymers with significant reductions in crystallinity, from 70.1% for PHB films to 41.5% for its composite with a 30% (w/w) loading of PEG2000. Blending also enabled manipulation of the material properties, increasing film flexibility with an extension to break of 2.49±1.01% for PHB films and 8.32±1.06% for films containing 30% (w/w) PEG106. Significant changes in the film surface properties, as measured by porosity, contact angles, and water uptake, were also determined as a consequence of the blending process, and these supported greater adhesion and proliferation of neural-associated olfactory ensheathing cells (OECs). A growth rate of 7.2×105 cells per day for PHB films with 30% (w/w) PEG2000 loading compared to 2.5×105 for PHB films was observed. Furthermore, while cytotoxicity of the films as measured by lactate dehydrogenase release was unaffected, biocompatibility, as measured by mitochondrial activity, was found to increase. It is anticipated that fine control of PEG composition in PHB-based composite biomaterials can be utilised to support their applications in medicinal and tissue engineering applications.